A review of marine sediment sampling methods. Issue 3 (17th September 2020) - Tuit, CB; Wait, AD
Abstract: This review summarizes sampling and quality control practices recommended by regulatory agencies and scientific organizations for acquiring reliable, defensible sediment samples in marine environments. Selecting an appropriate sediment sampling method can depend on water depth, sediment type, depth of sediment penetration required, and the study's data quality objectives, among other factors. The primary concern of most sediment sampling methods is preserving sediment stratigraphy and chemical gradients, particularly at the sediment-water interface, while avoiding contamination. Quality control samples and ancillary observations and measurements are also critical to sediment sample interpretation and reliability as part of Natural Resource Damage Assessment.